2002
DOI: 10.1074/jbc.m208063200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Serine 256 Suppresses Transactivation by FKHR (FOXO1) by Multiple Mechanisms

Abstract: FKHR is a member of the FOXO subfamily of Forkhead transcription factors, which are important targets for insulin and growth factor signaling. FKHR contains three predicted protein kinase B phosphorylation sites (Thr-24, Ser-256, and Ser-319) that are conserved in other FOXO proteins. We have reported that phosphorylation of Ser-256 is critical for the ability of insulin and insulin-like growth factors to suppress transactivation by FKHR (Guo, S., Rena, G., Cichy, S., He, X., Cohen, P., and Unterman, T. (1999)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
241
2
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(273 citation statements)
references
References 46 publications
24
241
2
2
Order By: Relevance
“…Furthermore, impairment of E2F1 nucleocytoplasmic shuttling in undifferentiated keratinocytes significantly increases apoptosis . Nuclear exclusion is an important mechanism to limit the effects of a number of transcription factors on gene expression, and changes in phosphorylation status can regulate their nuclear exit (Zhang et al, 2002). We propose that p38-dependent phosphorylation of S403 and T433 regulates several aspects of E2F1 function in keratinocytes.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, impairment of E2F1 nucleocytoplasmic shuttling in undifferentiated keratinocytes significantly increases apoptosis . Nuclear exclusion is an important mechanism to limit the effects of a number of transcription factors on gene expression, and changes in phosphorylation status can regulate their nuclear exit (Zhang et al, 2002). We propose that p38-dependent phosphorylation of S403 and T433 regulates several aspects of E2F1 function in keratinocytes.…”
Section: Discussionmentioning
confidence: 93%
“…⌬256FoxO1 still has two intact Akt phosphorylation sites, Thr 24 and Ser 253 (22). It has been reported that phosphorylation of the first and second Akt phosphorylation sites can affect DNA binding and regulate transcriptional activity of FoxOs (5,36,38,42). Therefore, loss of PDK-1 may enhance DNA binding of ⌬256FoxO1, and ⌬256FoxO1 can inhibit STAT3 binding to Pomc promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sites for both phosphorylation and acetylation have been identified within the FOXO1 protein (54). The Ab used in this study is specific for Ser 256 , a site phosphorylated by Akt (55). Btk may regulate phosphorylation at other sites that would not be detected with this reagent.…”
Section: Discussionmentioning
confidence: 99%